Factors Influencing Growth of Family Businesses in Jordan: A Comparative Study of Founders’ and Successors’ Perspectives - Mohmad, Abdin (2014)
Scholars are highly concerned with studying many affairs related to family firms. This dissertation aims to explore the different perceptions held by founders and successors as to the factors influencing the growth of a family business. It is very important for family members to understand the effect of different factors on the growth and survival of their firms. The factors are explored from diversified sectors and multigenerational members. It will discuss and analyze those factors and perceptions from the standpoint of family firms in Jordan. The factors affecting firm growth will be thoroughly examined through the analysis of a set of interviews conducted with a host of founders and successors. Key words: Family business, succession, founders, successors, entrepreneurship, growth, development, survival, factors of growth and perceptions of founders and successors.